Reduction Method Using Minimum Supply And Demand Method to Find an Initial Basic Feasible Solution of Transportation Problem - Morade, N.M (International Journal of Computer Sciences and Engineering, 2019)
Transportation Problem plays an important role in our economy and managerial decision- making. The main objective of transportation problem solving method is to obtain an optimal solution. An initial basic feasible solution is the first step to obtain an optimal solution for the transportation problems. Among the existing methods, Vogel’s Approximation Method gives an initial basic feasible solution near to the optimal solution, but it is very expansive in term of the execution of time. This paper introduces a new method, Reduction Method using minimum supply & demand method, to find an initial basic feasible solution of Transportation Problem. This method is easy to apply and fast compared to Vogel’s Approximation Method. It gives better initial basic feasible solution compared to all existing prominent methods. The method is also illustrated with numerical examples.